In vitro Characterization of Anti-SARS-CoV-2 Intravenous Immunoglobulins (IVIg) Produced From Plasma of Donors Immunized With the BNT162b2 Vaccine and Its Comparison With a Similar Formulation Produced From Plasma of COVID-19 Convalescent Donors - Rojas-Jiménez, Gabriel; Solano, Daniela; Segura, Álvaro; Sánchez, Andrés; Chaves-Araya, Stephanie; Herrera, María; Vargas, Mariángela; Cerdas, Maykel; Calvo, Gerardo; Alfaro, Jonathan; Molina, Sebastián; Bolaños, Kimberly; et al. (Frontiers in Medical Technology, 2022)
Despite vaccines are the main strategy to control the ongoing global COVID-19 pandemic, their effectiveness could not be enough for individuals with immunosuppression. In these cases, as well as in patients with moderate/severe COVID-19, passive immunization with anti-SARS-CoV-2 immunoglobulins could be a therapeutic alternative. We used caprylic acid precipitation to prepare a pilot-scale batch of anti-SARS-CoV-2 intravenous immunoglobulins (IVIg) from plasma of donors immunized with the BNT162b2 (Pfizer-BioNTech) anti-COVID-19 vaccine (VP-IVIg) and compared their in vitro efficacy and safety with those of a similar formulation produced from plasma of COVID-19 convalescent donors (CP-IVIg). Both formulations showed immunological, physicochemical, biochemical, and microbiological characteristics that meet the specifications of IVIg formulations. Moreover, the concentration of anti-RBD and ACE2-RBD neutralizing antibodies was higher in VP-IVIg than in CP-IVIg. In concordance, plaque reduction neutralization tests showed inhibitory concentrations of 0,03-0,09 g/L in VP-IVIg and of 0,06-0,13 in CP-IVIg. Thus, VP-IVIg has in vitro efficacy and safety profiles that justify their evaluation as therapeutic alternative for clinical cases of COVID-19. Precipitation with caprylic acid could be a simple, feasible, and affordable alternative to produce formulations of anti-SARS-CoV-2 IVIg to be used therapeutically or prophylactically to confront the COVID-19 pandemic in middle and low-income countries.